Branding Strategy in B2B Business: a Case Study of PT Multibina Teknika Utama - Astari Khairunnisa Isnan (Sean Institute, 2025)
This study examines the branding challenges of PT Multibina Teknika Utama, a B2B distributor of laboratory equipment in Indonesia. Although the company has strong technical capability and good after-sales service, its brand visibility is low because it rarely appears in Google search results, is difficult to find on e-Katalog LKPP, and has inconsistent product content and digital presentation. These issues make new buyers unaware of the company unless they receive recommendations. The research aims to (analyze Multibina’s current B2B branding strategy and propose solutions to improve its brand awareness and corporate image. A qualitative method was used through semi-structured interviews with internal staff and institutional buyers, supported by digital observations. The data were analyzed using thematic analysis and gap analysis. The findings show five key issues: low discoverability, weak digital content, strong service-based trust, increasing digital expectations from buyers, and limited internal capability for branding. Based on these findings, the study recommends improving digital visibility, standardizing product content, strengthening digital credibility, and developing internal readiness to support branding activities.